Some New Inequalities Involving κ-Fractional Integral for Certain Classes of Functions and Their Applications - Shuang-Shuang Zhou; Saima Rashid; Silvestru Sever Dragomir; Muhammad Amer Latif; Ahmet Ocak Akdemir; Jia-Bao Liu (Journal of Function Spaces)
In this article, we present several new inequalities involving the κ-fractional integral for the integrable function ℱ which satisfies one of the following conditions: aℱq is preinvex for some q>1; bℱ′ is bounded; cℱ′ is a Lipschitz function. As applications, we establish new inequalities for the weighted arithmetic and generalized logarithmic means.